Comparison of Errors Using Two Length-Based Tape Systems for Prehospital Care in Children. (3rd July 2016) - Rappaport, Lara D.; Brou, Lina; Givens, Tim; Mandt, Maria; Balakas, Ashley; Roswell, Kelley; Kotas, Jason; Adelgais, Kathleen M.
Abstract: Background: The use of a length/weight-based tape (LBT) for equipment size and drug dosing for pediatric patients is recommended in a joint statement by multiple national organizations. A new system, known as Handtevy™, allows for rapid determination of critical drug doses without performing calculations.Objective: To compare two LBT systems for dosing errors and time to medication administration in simulated prehospital scenarios.Methods: This was a prospective randomized trial comparing the Broselow Pediatric Emergency Tape™ (Broselow) and Handtevy LBT™ (Handtevy). Paramedics performed 2 pediatric simulations: cardiac arrest with epinephrine administration and hypoglycemia mandating dextrose. Each scenario was repeated utilizing both systems with a 1-year-old and 5-year-old size manikin. Facilitators recorded identified errors and time points of critical actions including time to medication.Results: We enrolled 80 paramedics, performing 320 simulations. For Dextrose, there were significantly more errors with Broselow (63.8%) compared to Handtevy (13.8%) and time to administration was longer with the Broselow system (220 seconds vs. 173 seconds). For epinephrine, the LBTs were similar in overall error rate (Broselow 21.3% vs. Handtevy 16.3%) and time to administration (89 vs. 91 seconds). Cognitive errors were more frequent when using the Broselow compared to Handtevy, particularly with dextrose administration. The frequency of procedural errors was similar between the two LBT systems.Conclusion: In simulated prehospital scenarios, use of the Handtevy LBT system resulted in fewer errors for dextrose administration compared to the Broselow LBT, with similar time to administration and accuracy of epinephrine administration.